2010
DOI: 10.1007/s11033-010-0625-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SbGSTU (tau class glutathione S-transferase) gene isolated from Salicornia brachiata in tobacco for salt tolerance

Abstract: Tau class glutathione transferases (GSTU) genes are plant specific, induced by different abiotic stress, and important for protecting plants against oxidative damage. GST gene was isolated using 5' RACE from an extreme halophyte Salicornia brachiata, cloned, sequenced and its protein structure was predicted. Transcript profiling of SbGST gene expression was studied under different abiotic stress conditions and plant growth regulator treatments, viz. salt, cold, drought, ABA and salicylic acid, with time period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
92
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(97 citation statements)
references
References 50 publications
5
92
0
Order By: Relevance
“…These characteristics allow vascular plants to adapt well to land living. Tau GSTs play important roles in plant detoxification metabolism, stress tolerance, and light signaling (Loyall et al, 2000;Thom et al, 2002;Benekos et al, 2010;Jha et al, 2011). The origin and expansion of tau GSTs in vascular plants might be correlated with their broad adaptations to land living.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics allow vascular plants to adapt well to land living. Tau GSTs play important roles in plant detoxification metabolism, stress tolerance, and light signaling (Loyall et al, 2000;Thom et al, 2002;Benekos et al, 2010;Jha et al, 2011). The origin and expansion of tau GSTs in vascular plants might be correlated with their broad adaptations to land living.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide analysis of biochemical characteristics of Arabidopsis (Arabidopsis thaliana) and poplar (Populus trichocarpa) tau and phi GSTs found that these two classes of GSTs have broad substrate specificities (Dixon et al, 2009;Lan et al, 2009), which may be related to the high tolerance to abiotic stresses, especially to a broad spectrum of xenobiotics. Overexpression of tau or phi GSTs increases tolerance to herbicides, salt, and UV stressors in transgenic plants (Karavangeli et al, 2005;Benekos et al, 2010;Jha et al, 2011), indicating a protective role against abiotic stress. Recently, Arabidopsis GSTF2 was found to selectively bind the indole-derived phytoalexin camalexin and the flavonol quercetin-3-O-rhamnoside, suggesting a role in regulating the binding and transport of defense-related compounds in plants (Dixon et al, 2011).…”
mentioning
confidence: 99%
“…Some species of Salicornia have shown important biological properties, such as antioxidant, anti-inflammatory, hypoglycemic and cytotoxic activities (Isca, Seca, Pinto, & Silva, 2014). Furthermore, Salicornia is being widely explored for abiotic stress-responsive genes and promoters to develop transgenic plants that can withstand adverse environmental conditions (Chaturvedi, Mishra, Tiwari, & Jha, 2012;Chaturvedi, Patel, Mishra, Tiwari, & Jha, 2014;Jha, Sharma, & Mishra, 2011;Singh, Mishra, & Jha, 2014a, 2014bUdawat, Mishra, & Jha, 2014). No information is available, so far, on the metabolomics of this important succulent halophytic plant.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of GSTs can be induced by a range of abiotic and biotic stresses as well as xenobiotic compounds and phytohormones, such as drought, salt, cold, heavy metals, 1 chloro 2,4 dinitrobenzene (CDNB), cyhalotrin, juglone, auxin, ABA, salicylic acid (SA), H 2 O 2 , herbicides, pathogens, and elicitor [13][14][15][16][17][18][19][20][21]. Previous studies indicated that plant GSTs play important roles not only during normal develop ment but also in detoxification of cytotoxic endoge nous and xenobiotic compounds as well as in response to a wide variety of stress conditions.…”
Section: Introductionmentioning
confidence: 99%